Demonstration Method, its influence on Knowledge and Practice of Baby Massage among Traditional Birth Attendants - Mayestika Eka Nur Fitriana; Siti Rofi'ah; Munayarokh Munayarokh (Poltekkes Kemenkes Semarang, 2019)
Background: The community still uses the power of a Traditional Birth Attendant (TBA) as infant massager because the TBA is considered to provide help with emotional security through prayers and is considered to be part of the social and cultural environment. Herbalists in villages typically show non-conforming massage methods and are even at risk for trauma injury to infants, the most dangerous of which TBA perform inappropriate massage on the abdomen and head.Purpose: The purpose of this research is to know the effect of health education by way of demonstration method for TBA in work area of Selopampang and Tembarak Public Health Center, Temanggung RegencyMethods: This study used pre experimental studies with one group of pretest - posttest design and qualitative and quantitative types. Sampling technique is by total sampling. All samples were given a questionnaire to measure the level of education and practice for infant massage.Result: The results showed that demonstration is the effective method for improving knowledge and practice with the result of T-Test statistical analysis p-value 0.000.Conclusion: It is expected that health personnel need to update the concepts needed to train children and children can apply the skills in accordance with the theory, so as to produce maximum results to create the next generation of quality.